Role of Superoxide Anions in the Redox Changes Affecting the Physiologically Occurring Cu(I)-Glutathione Complex. (20th September 2011) - Speisky, Hernán; López-Alarcón, Camilo; Olea-Azar, Claudio; Sandoval-Acuña, Cristian; Aliaga, Margarita E.
Abstract : The physiologically occurring copper-glutathione complex, [Cu(I)-[GSH]2 ], has the ability to react continually with oxygen, generating superoxide anions (O 2 ∙ - ). We addressed here the effects that superoxide removal has on the redox state of Cu(I) and GSH present in such complex and assessed the formation of Cu(II)-GSSG as a final oxidation product. In addition, we investigated the potential of a source ofO 2 ∙ - external to the Cu(I)-[GSH]2 complex to prevent its oxidation. Removal ofO 2 ∙ - from a Cu(I)-[GSH]2 -containing solution, whether spontaneous or Tempol-induced, led to time-dependent losses in GSH that were greater than those affecting the metal. The losses in GSH were not accompanied by increments in GSSG but were largely accounted for by the cumulative formation of Cu(II)-GSSG molecules. Notably, the redox changes in Cu(I) and GSH were totally prevented when Cu(I)-[GSH]2 was coincubated with hypoxanthine/xanthine oxidase. Data suggest that the generation ofO 2 ∙ - by Cu(I)-[GSH]2 implies the obliged formation of an intermediate whose subsequent oxidation into Cu(II)-GSSG or back reduction into Cu(I)-[GSH]2 is favoured by either the removal or the addition ofO 2 ∙ -, respectively.